Phase Fluctuation Cancellation for Uplink Radar Arrays Based on Passive Frequency Mixing - Zonglei Li; Lianshan Yan; Bin Luo; Wei Pan (IEEE Photonics Journal)
Precise time-difference detections among different radars in uplink radar arrays require ultrastable phase transfer in bidirectional analog optical fiber links. We propose and demonstrate a scheme based on passive frequency mixing to satisfy this requirement in which two continue wave (CW) radio frequency (RF) signals after passing through double-path of the transport fiber are utilized for dynamic phase fluctuation cancellation in uplink and downlink, respectively. Our scheme has the capabilities on stable phase transfers for both CW and pulsed RF signals. Experimental results show that the phase stability improvements in uplink and downlink are greater than a factor of 30 and a factor of 20 for 2.4-GHz RF signals over a 2-h measurement period along 25-km single mode fiber.